Examining EFL students' ISEB and OSEL amidst internet-based online learning environment during COVID-19 pandemic - Margareta Lisa Merrynda; Ive Emaliana; Hamamah Hamamah (Journal on English as a Foreign Language, 2022)
Students are becoming adapted to online self-regulated learning (hereafter, OSEL), which is closely related to students' internet-specific epistemic beliefs (hereafter, ISEB), as the internet became an important platform for the teaching process during the Coronavirus disease (COVID-19) pandemic. This study is aimed at researching the relationship between OSEL and ISEB among EFL students and after establishing the prediction. Data were collected through the questionnaires using the ISEB questionnaire (Kammerer et al., 2015) and the OSEL questionnaire (Zheng et al., 2016). Approximately 140 undergraduate students enrolled in the seventh semester of the English language education study program at a reputable university in Malang, Indonesia involved in this study. Interviews were then conducted to confirm the findings obtained from the questionnaires. The findings showed a substantial correlation between EFL students' ISEB and OSEL, with a correlation coefficient .555 and p-value .000. It also predicted that the higher EFL students' ISEB, the higher their OSEL too. The interview results elucidated support for this prediction. Students' ISEB and OSEL can help them solve their academic problems. Therefore, some pedagogical implications are described to promote better English learning, which uses the internet as one of the media of instruction.